1987
DOI: 10.1523/jneurosci.07-11-03588.1987
|View full text |Cite
|
Sign up to set email alerts
|

Electrically and chemically mediated increases in intracellular calcium in neuronal growth cones

Abstract: In the present report we used the calcium indicator fura-2 to compare intracellular levels of free calcium in growth cones of isolated Helisoma neurons under a variety of experimental conditions. We tested whether 2 different signals that inhibit growth cone motility--action potentials and serotonin--changed calcium levels in growth cones. Electrical stimulation of the cell body caused a rise in calcium levels at the growth cone. After brief stimulation, calcium levels quickly recovered to normal values, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
192
2
1

Year Published

1988
1988
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 283 publications
(213 citation statements)
references
References 27 publications
18
192
2
1
Order By: Relevance
“…Cellular mechanism of glutamate action Several lines of evidence have implicated calcium as a mediator of the effects of neurotransmitters and electrical activity on neuronal outgrowth (Cohan et al, 1987;Mattson andKater, 1987, Mattson et al, 1987) and survival (Coyle et al, 198 1;Berdichevsky et al, 1983;Coyle et al, 1981;Donaldson et al, 1983;Mayer and Westbrook, 1987). Studies in invertebrate central neurons demonstrated that serotonin and electrical activity can suppress neurite outgrowth by causing calcium influx (Cohan et al, 1987;Mattson and Kater, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cellular mechanism of glutamate action Several lines of evidence have implicated calcium as a mediator of the effects of neurotransmitters and electrical activity on neuronal outgrowth (Cohan et al, 1987;Mattson andKater, 1987, Mattson et al, 1987) and survival (Coyle et al, 198 1;Berdichevsky et al, 1983;Coyle et al, 1981;Donaldson et al, 1983;Mayer and Westbrook, 1987). Studies in invertebrate central neurons demonstrated that serotonin and electrical activity can suppress neurite outgrowth by causing calcium influx (Cohan et al, 1987;Mattson and Kater, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in invertebrate central neurons demonstrated that serotonin and electrical activity can suppress neurite outgrowth by causing calcium influx (Cohan et al, 1987;Mattson and Kater, 1987). Serotonin apparently induced calcium influx by activating voltage-dependent calcium channels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to different brain regions, where a downregulation was observed for mGluR5 (Romano et al, 1996), mGluR1␣ and mGluR5a were upregulated during postnatal retinal development. It has been shown that intracellular levels of free Ca 2ϩ influence neurite elongation and growth cone movement during development (Cohan et al, 1987) and that group I mGluRs are important for neuronal survival during development (Nicoletti et al, 1996;Pizzi et al, 1996). Because of the early appearance of group I mGluRs before synaptogenesis in the rat retina, they could influence synaptic differentiation during postnatal development and also might play …”
Section: Postnatal Retinal Development Of Group I Mglur Expressionmentioning
confidence: 99%